Seven contemporary plays from the Korean diaspora in the Americas - Lee, Esther Kim (Duke University Press, 2012)
History K / Edward Bok Lee -- 99 histories / Julia Cho -- American Hwangap / Lloyd Suh -- Hongbu & Nolbu: the tale of the magic pumpkins / Jean Yoon -- Yi Sang counts to thirteen / Sung Rno -- Satellites / Diana Son -- Mina / Kyoung H. Park